The Efforts to Improve Educator Professionalism through Madrasah Principal Leadership and Tsanawiyah Madrasah Educator Discipline - Ahmad Suganda; Rumbang Sirojudin; Wasehudin Wasehudin (Attractive : Innovative Education Journal, 2026)
This study examined the effects of administrator leadership and teacher discipline on the professionalism of educators in madrasahs in Serang Regency using a quantitative approach. The purpose of this research was to investigate the influence of principal leadership and teacher discipline on teacher professionalism, as well as the interaction between these two factors. Data were collected through a survey involving 63 respondents from madrasahs in Serang Regency. The findings indicate that stronger principal leadership, supported by higher levels of teacher discipline, contributes significantly to the improvement of teacher professionalism. Principal leadership accounted for 83.72% of the influence on teacher professionalism, while teacher discipline contributed 22.15%, and the interaction between principal leadership and teacher discipline contributed 17.20%. This study contributes to the educational leadership literature by providing empirical evidence that effective principal leadership is the dominant factor in enhancing teacher professionalism while demonstrating that teacher discipline strengthens this relationship. The findings offer practical insights for policymakers and school administrators in designing leadership development and teacher management strategies to improve the quality of education in madrasahs.